ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Kelvin, Seng; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to prove empirically the effect of current ratio, debt to equity ratio, asset turnover, and firm size on profitability in property and real estate companies. This study uses 90 data samples that selected by using purposive sampling method. The data used are secondary data in the form of company annual reports. The object in this study is a property and real estate company listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The data are processed using Eviews12. The results of this research indicate that asset turnover and firm size has a positive effect on profitability and debt to equity ratio has a negative effect on profitability, while current ratio has no effect on profitability.